Fungal Microbiota in Chronic Airway Inflammatory Disease and Emerging Relationships with the Host Immune Response - Zhang, Irene; Pletcher, Steven D.; Goldberg, Andrew N.; Barker, Bridget M.; Cope, Emily K. (Frontiers in Microbiology, 2017)
The respiratory tract is a complex system that is inhabited by niche-specific communities of microbes including bacteria, fungi, and viruses. These complex microbial assemblages are in constant contact with the mucosal immune system and play a critical role in airway health and immune homeostasis. Changes in the composition and diversity of airway microbiota are frequently observed in patients with chronic inflammatory diseases including chronic rhinosinusitis (CRS), cystic fibrosis, allergy, and asthma. While the bacterial microbiome of the upper and lower airways has been the focus of many recent studies, the contribution of fungal microbiota to inflammation is an emerging research interest. Within the context of allergic airway disease, fungal products are important allergens and fungi are potent inducers of inflammation. In addition, murine models have provided experimental evidence that fungal microbiota in peripheral organs, notably the gastrointestinal (GI) tract, influence pulmonary health. In this review, we explore the role of the respiratory and GI microbial communities in chronic airway inflammatory disease development with a specific focus on fungal microbiome interactions with the airway immune system and fungal-bacterial interactions that likely contribute to inflammatory disease. These findings are discussed in the context of clinical and immunological features of fungal-mediated disease in CRS, allergy, and asthmatic patients. While this field is still nascent, emerging evidence suggests that dysbiotic fungal and bacterial microbiota interact to drive or exacerbate chronic airway inflammatory disease.